Pengaruh Bokashi Kandang Ayam dan Npk Phonska terhadap Pertumbuhan dan Hasil Tanaman Jagung Manis (Zea mays saccharate sturt) - Ajun Permana; Kahar Kahar; Fandi Ahmad (Program Studi Agroteknologi, Fakultas Pertanian Universitas Madako Tolitoli, 2026)
This study aimed to determine the effect of chicken manure bokashi and NPK Phonska fertilizer on the growth and yield of sweet corn (Zea Mays saccaharate sturt). The research was conducted at the Experimental Farm of the Faculty of Agriculture, Madako University Tolitoli, from March to May 2025, using a factorial Randomized Complete Block Design (RCBD) with two treatment factors. The first factor was the dosage of chicken manure bokashi (B), consisting of B0 = without bokashi, B1 = 5 tons/ha (1 kg/plot), and B2 = 10 tons/ha (2 kg/plot). The second factor was the dosage of NPK Phonska fertilizer (N), consisting of N0 = without NPK, N1 = (80 g/plot or equivalent to 6 g/plant), and N2 = (140 g/plot or equivalent to 11 g/plant). Each treatment combination was replicated three times, resulting in 27 experimental plots. The results showed a significant interaction between chicken manure bokashi and NPK Phonska fertilizer on plant height, number of leaves, fresh cob weight, cob weight with husk, cob length, and number of kernels per row. The best combination was obtained with B2N2 (bokashi 10 tons/ha and NPK Phonska 700 kg/ha), producing a plant height of 166.06 cm, 7.00 leaves, fresh cob weight of 398.06 g, cob weight with husk of 567.78 g, cob length of 22.00 cm, and 40.61 kernels per row.